1997
DOI: 10.1007/bf01834073
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical procedures for degenerative lumbar spinal stenosis: A meta-analysis of the literature from 1975 to 1995

Abstract: Therapy for spinal stenosis remains difficult. The possibilities for conservative management are limited and not satisfactory in the more severe cases. Various surgical procedures are possible, such as decompression, decompression and fusion without instrumentation and decompression and fusion with instrumentation. The aim of our metaanalysis was to compare the postoperative results of these three surgical techniques in the literature and, thus, to establish a treatment of choice for degenerative lumbar spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1
5

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 23 publications
3
41
1
5
Order By: Relevance
“…The degree of stenosis determines the indication for mono-or bilateral hemifacetectomy, mono-or bilateral laminectomy or even laminectomy on two levels. A meta-analysis of the literature from 1975 to 1995 revealed that decompressive laminectomy is only optimal for degenerative spinal stenosis if symptoms have a duration of less than 8 years [13]. Another meta-analysis also showed that decompressive laminectomy can benefit many patients with lumbar spinal stenosis by reducing pain and increasing function [22].…”
mentioning
confidence: 99%
“…The degree of stenosis determines the indication for mono-or bilateral hemifacetectomy, mono-or bilateral laminectomy or even laminectomy on two levels. A meta-analysis of the literature from 1975 to 1995 revealed that decompressive laminectomy is only optimal for degenerative spinal stenosis if symptoms have a duration of less than 8 years [13]. Another meta-analysis also showed that decompressive laminectomy can benefit many patients with lumbar spinal stenosis by reducing pain and increasing function [22].…”
mentioning
confidence: 99%
“…In all but the most moderate of cases, the problem is difficult to treat without recourse to surgery [5-7, 20, 25], due to the largely mechanical (structural) nature of the disorder [57]. Nonetheless, the success rates of surgery are not particularly impressive: systematic reviews of the long-term outcome report an average success rate of between 45 and 72%, depending on the criterion by which 'success' is judged (ability to work, neurologic symptoms, leg/back pain) [16,43,58].…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of those studies favours surgical over conservative treatment [2,16]. The most widely used surgical techniques are all based on the principles of decompression alone or decompression and fusion, with or without instrumentation [8,11,21,24].…”
Section: Introductionmentioning
confidence: 99%